Evaluation of a Novel Nutrition Supplement on Cognitive Function and Cerebral Blood Flow in Young Children Living in Rural Villages in Guinea-Bissau (OR10-02-19). (13th June 2019) - Taylor, Salima; Silver, Rachel; Franceschini, Maria; Muentener, Paul; Sa, Augusto Braima de; Co, Raimundo; Sonco, Aliu; Balé, Carlito; Saltzman, Edward; Roberts, Susan
Abstract: Objectives: Undernutrition is prevalent among young children worldwide and is associated with impaired cognition and reduced educational attainment. We conducted a randomized controlled trial to test the effect of a novel supplementary food (regenerative nutrition for enhanced wellness-cognition; RENEW-C) compared to traditional feeding practices on cognitive function, cerebral blood flow and oxygen metabolism in rural Guinea-Bissau. Methods: Children aged 15 months to 7 years ( n  = 1059) were randomized to receive isocaloric quantities of RENEW-C (a highly-fortified cocoa-based bar), a USAID fortified blended food (FBF) or a Control food (rice cooked with oil, replicating a traditional breakfast). The primary outcome was executive function. Secondary outcomes included a cerebral blood flow index (CBFi ) and cerebral metabolic rate of oxygen (CMRO2 ) measured by Frequency-Domain Near-Infrared Spectroscopy and Diffusion Correlation Spectroscopy (FDNIRS-DCS, MetaOx, ISS Inc.). Six-month changes for RENEW-C and FBF versus Controls were assessed by multivariable linear mixed models adjusted for age, sex, baseline measurement, and study cohort. Results: Improvements in executive function (0.38; 95% CI: 0.10, 0.71; P  = 0.02) were observed for RENEW-C compared to Controls in the predefined study focus (children < 4 years consuming >75% their supplement). There was no significant effect of RENEW-C in children ≥ 4 years. No benefit of the FBF was observed in either age group. In addition, changes in CBFi and CMRO2 in RENEW-C children were greater than in Controls in both ventrolateral prefrontal cortical regions ( P  = 0.03 and P  = 0.04 for left and right, respectively) and greater than FBF in the left ventrolateral ( P  = 0.05) and left dorsolateral ( P  = 0.03) prefrontal cortices. Conclusions: Compared with traditional feeding practices, the RENEW-C supplement consumption was correlated with a marked improvement in executive function among children < 4 years and large increases in vascular perfusion and oxygen metabolism in a region where undernutrition is prevalent. These results indicate that new approaches to formulating supplementary foods for children at risk of undernutrition can potentially yield substantial improvements in brain health and cognition. Funding Sources: Boston Foundation.